IL-9 Alters Epithelial Barrier and E-cadherin in Eosinophilic Esophagitis - Doshi, Ashmi (J Pediatr Gastroenterol Nutr, 2019)
BACKGROUND. Eosinophilic esophagitis (EoE) is a chronic Th2-assocated inflammatory condition accompanied by substantial impairments in epithelial barrier function and increased numbers of IL-9 expressing inflammatory cells. While IL-9 is known to affect barrier function in the intestine, the functional effects of IL-9 on the esophagus are unclear. Herein we aimed to understand the expression of the IL-9 receptor and effects of IL-9 on the epithelium in EoE. METHODS. We used esophageal biopsies from pediatric EoE patients with active and inactive disease to analyze the expression of the IL-9 receptor, the adherens junction protein E-cadherin and the tight junction protein claudin-1. We treated primary human esophageal epithelial cells with IL-9 to understand its effects on E-cadherin expression and function. RESULTS. Active EoE subjects had increased epithelial expression of IL-9 receptor mRNA and protein (p<0.05) and decreased membrane bound E-cadherin (p<0.01) and claudin-1 (p<0.05) expression. IL-9 receptor expression and mislocalized claudin-1 positively correlated and while membrane bound E-cadherin expression negatively correlated with the degree of histologic epithelial remodeling (p<0.05). IL-9 decreased epithelial resistance in stratified primary human esophageal epithelial cells (p<0.01) and membrane bound E-cadherin in epithelial cell monolayers (p<0.01). CONCLUSION. These data suggest that IL-9, its receptor, and its effects on E-cadherin may be important mechanisms for epithelial barrier disruption in EoE.